DFT study of the influence of acetyl groups of cellulose acetate on its intrinsic birefringence and wavelength dependence. (1st March 2019) - Hayakawa, Daichi; Gouda, Hiroaki; Hirono, Shuichi; Ueda, Kazuyoshi
Graphical abstract: Highlights: Wavelength dependence of Δn° of CA was calculated by DFT. Δn° significantly depends on the conformations of the acetyl group at C6. The ensemble average was calculated for the calculated Δn° values (<Δn°>). The results were in good agreement with the experimental birefringence. Conformational variety and its control are important for the CA optical film design. Abstract: The effect of the acetyl groups of cellulose acetate (CA) on its intrinsic birefringence and its wavelength dependence was investigated using density functional theory (DFT). Seven types of CA repeating-unit models that differ in their degree of substitution (DS) and substitution sites were used in the calculations. The results suggested that the intrinsic birefringence (Δn°) and its wavelength dependence significantly depended on the conformations of the acetyl group at C6. Additionally, the intrinsic birefringence of CA films was estimated as the ensemble average of the calculated Δn° values of the conformers. The increase in the DS of CA led to a more negative intrinsic birefringence and a larger wavelength dependence. The computational results were in good qualitative agreement with the experimental results and suggested that conformational variety and/or its control would be important factors for the design of optical films containing CA.